Desain Strategi Pembelajaran Menuju Capaian Pembelajaran - Abd. Muqit; Djuwairiyah Djuwairiyah (Program Pascasarjana Universitas Ibrahimy, 2017)
The purpose of education is first and foremost. To achieve the components of learning from each other to be interrelated and integrated (systemic-organic). Learning components may include at least learners (leaner), educators, curriculum, teaching materials, source materials, media, evaluation, environmental, objectives and learning process. So that the goal is reached, all components must be organized well between each other resulting in an integrative cooperation. Therefore, teachers must not only pay attention to certain components, but have to consider those components as a whole. The learning process is an important thing to be considered by the manager of education. It is at least cover; approaches, strategies, methods, techniques, tactics, models, and designs. Design learning strategy is a necessity to achieve the learning objectives, namely to establish a framework or plan learning approach as a systematic way of communicating learning materials for learners to achieve the learning objectives. The learning objectives can be achieved effectively and efficiently relies heavily on learning strategies. In determining and developing learning strategies should at least pay attention to the learning objectives, characteristics of the field of study, circumstances and conditions of the students. With good design learning strategies can deliver the expected achievement of learning objectives.